Gut microbiota, circulating metabolites, and pancreatic cancer risk: a multi-method causal inference study with cross-population validation - Lin, Shicheng; Shi, Enze; Zhang, Yuxin; Wang, Xiaofan; Tian, Zhen; Han, Jing; Li, Quanwang (Frontiers in Microbiology, 2026)
Pancreatic cancer (PC) is a lethal malignancy with limited early detection strategies and poor therapeutic response. Emerging evidence implicates the gut microbiota in carcinogenesis, yet whether microbial alterations are causal or secondary remains uncertain. In this study, we integrated cross-sectional 16S rDNA sequencing, two-sample Mendelian randomization (MR), and mediation analysis to investigate the causal role of gut microbiota in PC risk. We profiled fecal microbiota in a Beijing-based cohort of 26 newly diagnosed PC patients and 9 healthy controls, revealing significant dysbiosis characterized by reduced microbial diversity, depletion of butyrate-producing genera (e.g., Faecalibacterium), and enrichment of pro-inflammatory taxa such as Olsenella. Using European GWAS summary data, MR analysis identified 17 gut microbial taxa causally associated with PC risk, including Olsenella and Pauljensenia sp000411415. Notably, higher abundance of Pauljensenia sp000411415 was associated with increased PC risk, an effect partially mediated by reduced circulating levels of octanoylcarnitine (C8) and glutarylcarnitine (C5-DC)—metabolites independently linked to lower PC risk. Population-matched MR in East Asian cohorts validated several causal associations, enhancing ancestral relevance. Our findings support a causal role for specific gut microbes in pancreatic carcinogenesis and highlight a Pauljensenia–acylcarnitine axis whereby microbial suppression of protective metabolites may contribute to disease development. This integrative approach bridges microbial dysbiosis with functional mechanisms, offering novel insights for microbiome-informed strategies in PC prevention and early detection.